Implementation of Modern Agricultural Food System in Timor-Leste, 1982-2007 - Joaquina Tavares; Yety Rochwulaningsih; Haryono Rinardi (Diponegoro University, 2021)
This article examines modern process of agriculture in Timor-Leste in the period of 1982 and 2007. The modern agricultural system has been conducted in the 1980s, when the Indonesian government worked together with a non-governmental organization (NGO), namely the East Timor Agricultural Development Program (ETADEP) to overcome famine during the civil war in the region. The Indonesian government and the NGO ETADEP have modernized farmers by using tractor machines to cultivate the land, but at that time 95% were categorized as traditional farmers. Thus, it was difficult for them to implement modern agriculture at that time. This article uses the historical method which includes four stages, including heuristics, source criticism, interpretation, and historiography. The modern process of agriculture in Timor Leste has been conducted since 1982 when was marked by the implementation of the Mass Guidance program (BIMAS). Through the Bimas program, the government has succeeded in developing farmers' business credit to facilitate the credit provision in the form of agricultural tools and inputs to the farmers. After its independence, Timor-Leste faced new challenges in food self-sufficiency. The adoption and adaptation of new technologies in organic farming, such as the Intensive Design System (SRI) and Integrated Crop Management (ICM) are organic farming technologies. However, SRI and ICM replaced the modern agricultural system which had been adopted from Indonesia. Since 2007, the implementation of both the SRI and ICM models have been continued to date. The Timor-Leste government has made great efforts to implement SRI and ICM organic farming eventhough the implementation of both models is considered troublesome for farmers and indirectly resulted the failure of food self-sufficiency policy in Timor-Leste.